Temporal phase unwrapping using orthographic projection. (March 2017) - Petković, Tomislav; Pribanić, Tomislav; Đonlić, Matea
Abstract: This paper proposes a novel temporal phase unwrapping method which is a generalization of the three commonly proposed approaches: hierarchical, heterodyne, and number theoretical phase unwrapping. The proposed unwrapping method is based on the orthographic projection of wrapped phases from the measurement space to the space of co-dimension 1. In the space of co-dimension 1 all unknown integer period-order numbers are computed simultaneously using a nearest-neighbor search on a fixed constellation of points. The proposed method offers new key insights about relationship between unwrapping success rate, noise limit, and maximum unwrapping range. We give example how the proposed method may be applied in the multiple frequency phase shifting profilometry. Abstract : Highlights: A temporal-phase unwrapping method using orthographic projection is proposed. The method generalizes hierarchical, heterodyne, and number-theoretical approaches. The method has minimal constraints on selected wavelengths. Direct link between noise and unwrapping success rate is given for n wavelengths. Basis-2 exponential frequency sequence has the largest noise tolerance.